2022
DOI: 10.3389/fimmu.2022.1008456
|View full text |Cite
|
Sign up to set email alerts
|

Autologous organoid co-culture model reveals T cell-driven epithelial cell death in Crohn’s Disease

Abstract: Lympho-epithelial interactions between intestinal T resident memory cells (Trm) and the epithelium have been associated with inflammatory bowel disease (IBD) activity. We developed ex vivo autologous organoid-mucosal T cell cocultures to functionally assess lymphoepithelial interactions in Crohn’s Disease (CD) patients compared to controls. We demonstrate the direct epithelial cell death induced by autologous mucosal T cells in CD patients but not in controls. These findings were positively correlated with T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…Our findings demonstrate that E-Cadherin co-stimulates CD8 + T cells as evident by the upregulation of CD69 and the secretion of cytotoxic mediators and suggest that this mechanism might be important in the context of IBD. Together with a previous report showing that the interaction of αEβ7 with E-Cadherin also drives T cell infiltration to epithelial organoids 36 , it emerges that αEβ7 is a key modulator of epithelial-lymphocyte crosstalk. However, while etrolizumab seems to be able to block adhesive lympho-epithelial interaction and cytotoxicity resulting from direct cell-to-cell contact of T lymphocytes with the epithelium 36 , our data suggest that co-stimulatory pathways leading to the secretion of soluble cytotoxic mediators are not sufficiently blocked and we therefore hypothesize that these mediators might cause epithelial cell death in the inflamed gut in a paracrine manner as demonstrated in the literature 37 , 38 .…”
Section: Discussionsupporting
confidence: 62%
“…Our findings demonstrate that E-Cadherin co-stimulates CD8 + T cells as evident by the upregulation of CD69 and the secretion of cytotoxic mediators and suggest that this mechanism might be important in the context of IBD. Together with a previous report showing that the interaction of αEβ7 with E-Cadherin also drives T cell infiltration to epithelial organoids 36 , it emerges that αEβ7 is a key modulator of epithelial-lymphocyte crosstalk. However, while etrolizumab seems to be able to block adhesive lympho-epithelial interaction and cytotoxicity resulting from direct cell-to-cell contact of T lymphocytes with the epithelium 36 , our data suggest that co-stimulatory pathways leading to the secretion of soluble cytotoxic mediators are not sufficiently blocked and we therefore hypothesize that these mediators might cause epithelial cell death in the inflamed gut in a paracrine manner as demonstrated in the literature 37 , 38 .…”
Section: Discussionsupporting
confidence: 62%
“…For instance, organoid‐immune cell co‐cultures (Support Protocol 3) could shed light on the interplay between MP/NP uptake by intestinal epithelial cells and immune responses by leukocytes (Rubio et al., 2020; Staab et al., 2020). Models of organoid‐immune cell co‐cultures have been established and used in investigation of inflammatory responses in the intestinal system (Hammoudi et al., 2022; Schreurs et al., 2021). Specifically, the presence of MP/NP exacerbated the severity of inflammatory bowel disease (IBD) and Crohn's Disease (CD) (Yan et al., 2022; Zhao et al., 2023).…”
Section: Commentarymentioning
confidence: 99%
“…T cells are known to drive the pathogenesis of intestinal inflammatory disorders due to excessive cytotoxicity and production of pro-inflammatory cytokines. T cells and organoids have been co-cultured indirectly using transwell systems (with T cells cultured in the basolateral chamber) [87], or directly by embedding both populations in an ECM [88,89]. Using the indirect coculture method, it was demonstrated that secretion of inflammatory mediators by T cells is sufficient to destroy colonoid monolayers [87].…”
Section: Epithelial Cell-cell Interactionsmentioning
confidence: 99%